The Influence of Self-esteem and Self-efficacy on Motivation in Completing Tasks among Students of Vocational School 1 Cilaku Cianjur - Wulansari, Siti; Meirawan, Danny; Purwanto, Dedy (Jurnal Pendidikan Teknik Bangunan, 2025)
Self-esteem can be defined as an individual's evaluation of themselves. Self-efficacy is an individual's belief in their ability to complete tasks and overcome problems. Ideally, if students have high levels of self-esteem and self-efficacy, they will also have high motivation to complete tasks. This research was conducted to understand the levels of self-esteem, self-efficacy, and motivation in task completion. Additionally, it aims to determine the influence of self-esteem and self-efficacy on motivation in task completion. The approach used is quantitative with associative and descriptive methods, and the data collection methods used are surveys and observations. The population involved consists of students from the Building Modeling and Information Design (DPIB) program at Vocational School 1 Cilaku Cianjur in Phase F. The sample size of the study is 55 students. Based on the data analysis results, it was found: (1) students at Vocational School 1 Cilaku Cianjur have a moderate level of self-esteem, (2) students at Vocational School 1 Cilaku Cianjur have a moderate level of self-efficacy, (3) the level of motivation in completing tasks among students at Vocational School 1 Cilaku Cianjur is at a moderate level, (4) there is a significant influence of self-esteem on the motivation to complete tasks among students at Vocational School 1 Cilaku Cianjur, (5) there is a significant influence of self-efficacy on the motivation to complete tasks among students at vocational school 1 Cilaku Cianjur, and (6) self-esteem and self-efficacy significantly affect students' motivation to complete tasks at Vocational School 1 Cilaku Cianjur